Decorating ZnO nanoflakes on carbon cloth: Free-standing, highly stable lithium-ion battery anodes. Issue 13 (September 2019) - Yan, Yaping; Wang, Bo; Yan, Changzeng; Kang, Dae Joon
Abstract: A facile chemical bath deposition method to grow 10-nm-thick ZnO nanoflakes (NFs) on carbon cloth (CC) was developed; further, free-standing, flexible lithium-ion -battery (LIB) anodes with good electrical contact between current collector and the active substance were prepared. The as-prepared ZnO NFs/CC-based LIB anodes showed a high specific capacity of 1754 mAh g −1 at a current density of 0.1 A g −1, a capacity retention of almost 52.9% at a current density of 2 A g −1, as well as high rate capability. Moreover, the anodes demonstrated a high capacity with reversiblity of approximately 1650 mAh g −1 and only 6% capacity fading at a current density of 0.1 A g −1, even after 100 cycles. These results imply that the synthesized, unique ZnO NFs/CC nanostructures can be employed as high-efficiency anode materials for flexible LIBs.